PENGARUH PENGETAHUAN PERPAJAKAN DAN TAX AMNESTY TERHADAP KEPATUHAN PERPAJAKAN WAJIB PAJAK ORANG PRIBADI PASCA TAX AMNESTY - Faturahman, Beny; Nurlaela, Siti; Masitoh, Endang (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan, 2018)
This study aims to determine the significance of the influence of taxation knowledge and tax amnesty on individual taxpayer tax compliance after tax amnesty. This study uses a questionnaire with an individual taxpayer population registered at the Sukoharjo Pratama Tax Service Office. The sample in this study is an individual taxpayer who follows the tax amnesty program registered at the Sukoharjo Pratama Tax Service Office. The sampling technique uses Non-Probability Sampling with a sample of 87 respondents. The data used in this study is a questionnaire using a Likert scale of 1 to 5. The data analysis technique used in this study is multiple linear regression using SPSS version 17 for Windows. Based on the results of the analysis carried out shows that there is influence of taxation knowledge and tax amnesty on individual taxpayer tax compliance after tax amnesty.